STRYCHNOS SPINOSA LAM: COMPREHENSIVE REVIEW ON ITS MEDICINAL AND NUTRITIONAL USES. - Tittikpina, Nassifatou Koko; Atakpama, Wouyo; Hoekou, Yao; Diop, Yerim Mbagnick; Batawila, Komlan; Akpagana, Komlan (African Journal of Traditional, Complementary and Alternative Medicines, 2023)
Background: Most of the people living in developing countries rely on local remedies from traditional medicines to take care of their healthcare needs. In recent years, the use of medicinal plants increased considerably. Consequently, studies on medicinal plants are necessary to produce more effective drugs with fewer side-effects. This work aims to compile the dispersal data on Strychnos spinosa Lam., a medicinal plant with great therapeutic potential in traditional medicine, on its ethnobotanical uses, chemical compounds, as well as its pharmacological and nutritional effects. Material and Methods: To achieve the aforementioned aim, electronic databases such as Pubmed, Science Direct, Google scholar, Scopus and SciFinder were scanned. Results: Literature survey revealed that S. spinosa is used in the treatment of microbial infections, malaria, trypanosomiasis, intestinal worms, tuberculosis, infertility, gastrointestinal disorders, snake bite, hypertension, and diabetes mellitus among other ailments. The plant is also used as food material. S. spinosa contains many chemical compounds, such as alkaloids, terpenes, sterols, fatty acids, flavonoids, saponin, and others. The fruits are a source of important nutrients such as carbohydrates, sugars, proteins, vitamins and fibres. Experimental studies have shown numerous pharmacological properties, including antimicrobial, antiplasmodial, anti-trypanosomal, anti-leishmanial, anti-nematicidal, anti-inflammatory, anti-oxidant, antidiabetic and other activities. Conclusion: This review article provides comprehensive information on S. spinosa and its various extracts. Due to the promising effects of the plant extracts on various diseases and its nutritional values, there is a need for toxicity studies and clinical trials to assess the effects of its identified bioactive compounds.